Confirmation of ovulation from urinary progesterone analysis: assessment of two automated assay platforms. Issue 1 (December 2018) - Gifford, Robert; Howie, Forbes; Wilson, Kirsten; Johnston, Neil; Todisco, Tommaso; Crane, Mike; Greeves, Julie; Skorupskaite, Karolina; Woods, David; Reynolds, Rebecca; Anderson, Richard
Abstract Urinary concentrations of the major progesterone (P4) metabolite pregnanediol-3-glucuronide (PDG) are used to confirm ovulation. We aimed to determine whether automated immunoassay of urinary P4 was as efficacious as PDG to confirm ovulation. Daily urine samples from 20 cycles in 14 healthy women in whom ovulation was dated by ultrasound, and serial weekly samples from 21 women in whom ovulation was unknown were analysed. Daily samples were assayed by two automated P4 immunoassays (Roche Cobas and Abbott Architect) and PDG ELISA. Serial samples were assayed for P4 by Architect and PDG by ELISA. In women with detailed monitoring of ovulation, median (95% CI) luteal phase increase was greatest for PDG, 427% (261–661), 278% (187–354) for P4 Architect and least for P4 Cobas, 146% (130–191), p < 0.0001. Cobas P4 also showed marked inaccuracy in serial dilution. Similar ROC AUCs were observed for individual threshold values and two-sample percent rise analyses for P4 Architect and PDG (both >0.92). In serial samples classified as (an)ovulatory by PDG, P4 Architect gave ROC AUC 0.95 (95% CI 0.89 to 1.01), with sensitivity and specificity for confirmation of ovulation of 0.90 and 0.91 at a cutoff of 1.67 μmol/mol. Automated P4 may potentially be as efficacious as PDG ELISA but research from a range of clinical settings is required.